Nutrient Transporter Gene Expression in the Early Conceptus—Implications From Two Mouse Models of Diabetic Pregnancy - Kappen, Claudia; Kruger, Claudia; Jones, Sydney; Salbaum, J. Michael (Frontiers in Cell and Developmental Biology, 2022)
Maternal diabetes in early pregnancy increases the risk for birth defects in the offspring, particularly heart and neural tube defects. While elevated glucose levels are characteristic for diabetic pregnancies, these are also accompanied by hyperlipidemia, indicating altered nutrient availability. We therefore investigated whether changes in the expression of nutrient transporters at the conception site or in the early post-implantation embryo could account for increased birth defect incidence at later developmental stages. Focusing on glucose and fatty acid transporters, we measured their expression by RT-PCR in the spontaneously diabetic non-obese mouse strain NOD, and in pregnant FVB/N mouse strain dams with Streptozotocin-induced diabetes. Sites of expression in the deciduum, extra-embryonic and embryonic tissues were determined by RNAscope in situ hybridization. While maternal diabetes had no apparent effects on levels or cellular profiles of expression, we detected striking cell-type specificity of particular nutrient transporters. For examples, Slc2a2/Glut2 expression was restricted to the endodermal cells of the visceral yolk sac, while Slc2a1/Glut1 expression was limited to the mesodermal compartment; Slc27a4/Fatp4 and Slc27a3/Fatp3 also exhibited reciprocally exclusive expression in the endodermal and mesodermal compartments of the yolk sac, respectively. These findings not only highlight the significance of nutrient transporters in the intrauterine environment, but also raise important implications for the etiology of birth defects in diabetic pregnancies, and for strategies aimed at reducing birth defects risk by nutrient supplementation.